2016
DOI: 10.1016/j.clbc.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Randomized Study of Lapatinib Combined With Capecitabine, Vinorelbine, or Gemcitabine in Patients With HER2-Positive Metastatic Breast Cancer With Progression After a Taxane (Latin American Cooperative Oncology Group 0801 Study)

Abstract: LV and LG seem to be active combinations in patients with HER2(+) MBC after taxane failure. The overall toxicity was manageable in all regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 29 publications
(45 reference statements)
1
26
0
Order By: Relevance
“…The most common grade 3 and 4 adverse events were hand-foot syndrome (18%), diarrhea (6-9%) and increased alanine aminotransferase/aspartate aminotransferase (4-13%) and neutropenia (36-47%). Progression-free survival and toxicity also matched with those from other studies of lapatinib-capecitabine and lapatinib-vinorelbine in similar populations [98].…”
Section: Hormonotherapy and Anti-her2 Therapysupporting
confidence: 73%
See 1 more Smart Citation
“…The most common grade 3 and 4 adverse events were hand-foot syndrome (18%), diarrhea (6-9%) and increased alanine aminotransferase/aspartate aminotransferase (4-13%) and neutropenia (36-47%). Progression-free survival and toxicity also matched with those from other studies of lapatinib-capecitabine and lapatinib-vinorelbine in similar populations [98].…”
Section: Hormonotherapy and Anti-her2 Therapysupporting
confidence: 73%
“…The overall response rate (ORR) went from 41 to 56% in the capecitabine, vinorelbine or gemcitabine arm [98] which compares with an ORR on previously published data of 11.1-59.3% [99]. The median progression-free survival went from 7 to 9 months.…”
Section: Hormonotherapy and Anti-her2 Therapymentioning
confidence: 63%
“…Though the direct comparison was not inappropriate, our analysis suggested that continued use of trastuzumab in the basis of standard LX treatment among patients had progression on trastuzumab may provide benefit. LACOG 0801 study investigated the efficacy and safety of lapatinib combined with capecitabine (LX), vinorelbine (V), or gemcitabine (G) in patients with HER2+ MBC with progression after a taxane (20). The results show that LX has similar efficacy with the other 2 arms, though LV has a more numerically longer median PFS and OS (20).…”
Section: Discussionmentioning
confidence: 99%
“…LACOG 0801 study investigated the efficacy and safety of lapatinib combined with capecitabine (LX), vinorelbine (V), or gemcitabine (G) in patients with HER2+ MBC with progression after a taxane (20). The results show that LX has similar efficacy with the other 2 arms, though LV has a more numerically longer median PFS and OS (20). Our results also showed that TL combined with capecitabine had a numerically longer median PFS than vinorelbine, similar to previously reported in LACOG0801 study, suggesting that the two regimens seem to be active combinations in HER2+ MBC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vinorelbine has been shown to be well tolerated in patients, with noncumulative granulocytopenia and neurotoxicity as the main dose-limiting toxicities. In several studies, the vinorelbine-based regimen showed significant antitumor activity and good tolerability for anthracycline- and taxane-pretreated ABC patients [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%